DEVELOPMENT OF THE CAPITAL MARKET AS A FACTOR OF SUSTAINABLE ECONOMIC GROWTH OF THE STATE - Karabayev Odiljon Muxsinovich; Muhsinova Mohizoda Odiljon qizi (Modern American Journals, 2025)
This article examines the role of the capital market in ensuring sustainable economic growth of the state. The capital market is an important tool that makes it possible to efficiently allocate financial resources, stimulate investment activity and facilitate access to finance for enterprises in the real sector of the economy. The article analyzes the current state of the capital market in Uzbekistan, its impact on macroeconomic indicators and development prospects. A number of measures are proposed aimed at further developing the capital market, including expanding the base of institutional investors, increasing the variety of financial instruments, improving market infrastructure, increasing data transparency and protecting investors' rights, as well as implementing programs to improve financial literacy of the population. The implementation of these measures can contribute to ensuring sustainable growth, economic diversification and increasing its competitiveness.
Keywords: Capital market, sustainable economic growth, financial resources, institutional investors, market capitalization, financial literacy, financial instruments, investments.